Surface heat flux analysis for opposing jet and combination techniques in the presence of real gas effect. (2022) - Patil, Ajay; Kulkarni, Vinayak
Abstract: High surface heating is common problem during high speed flights, so it should be properly mitigated for the efficient design of long duration flights. Most of the studies available in the literature are carried out without considering the chemical kinetics of the incoming freestream flow. Hence the current study invokes the thermal non-equilibrium effect (specific heats variation with temperature) and chemical non-equilibrium effect (species continuity equations) on surface heat flux study for the flow over blunt body considering real gas reactions by means of in house developed reacting and perfect gas solvers. Results reveal that surface heat flux reduces with the application of opposing jet and it further reduces for higher pressure ratio of jet. Introduction of cavity reduces the Stanton number but it enhances the drag force on body. Reacting solver gives higher surface heat flux than perfect solver and this difference is larger at low freestream stagnation enthalpy.